Relationships between Student Burnout, Mental Health, Study Habits and Sleep: A Cross-Sectional Study - Rodrigues Matos, Fabíola; Maria Malavasi, Reziele; De Andrade, Alexsandro Luiz (Pensando Psicología, 2025)
The demands of high performance in students seeking to enter higher education affect physical and psychological health when sickening habits are maintained by this population. This cross-sectional study with an analytical approach aimed to investigate student burnout, aspects of mental health and their relationships with study habits and sleep. 401 students participated in the research, the majority of whom were women (70.7%; n= 282), with an average age of 18.2 years (sd = 3.0), from a state in southeastern Brazil. Data were collected using the following structured questionnaires: Oldenburg Burnout Inventory (Student Version), Depression, Anxiety and Stress Scale for Adolescents (EDAE-A), Positive and Negative Affect Scale for Adolescents, and Sociodemographic Questionnaire to characterize the sample. Network analyses were conducted to investigate the association between study habits and constructs related to mental health, while descriptive statistics were conducted to characterize the sample. The results indicated above-average levels for negative affects, depression, and anxiety, as well as the association between exhaustion and the longer study time of the sample. Evidence is discussed that mental health can suffer damage according to the time dedicated to study and sleep.